A robust LQR-MPC control strategy with input constraints and control zones. (April 2018) - Capron, Bruno Didier Olivier; Odloak, Darci
Highlights: Robust control of systems with model uncertainty. Combination of Linear Quadratic Regulator with Model Predictive Control. Multi-model representation is considered. Approach can be applied to unstable systems. Abstract: In this paper, the robust control of a class of uncertain process systems with stable and unstable outputs that considers input constraints and control zones is addressed. In the proposed approach, a robust Linear Quadratic Regulator (LQR) controls the system outputs by manipulating the systems inputs and a robust Model Predictive Control (MPC) manipulates the output set-points to maintain the system outputs inside their zones and to enforce the input constraints and targets. The performance of the proposed controller is tested through the simulation of a low order industrial process.